2015
DOI: 10.1186/s12889-015-1501-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing children’s physical activity through a teaching-assistant led extracurricular intervention: process evaluation of the action 3:30 randomised feasibility trial

Abstract: BackgroundMany children do not engage in recommended levels of physical activity (PA), highlighting the need to find ways to increase children’s PA. Process evaluations play an important role in improving the science of randomised controlled trials. We recently reported the results of the Action 3:30 cluster randomised feasibility trial illustrating higher levels of moderate to vigorous intensity PA among boys but not girls. The aim of this paper is to report the process evaluation results including interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 33 publications
2
31
1
Order By: Relevance
“…Similarly to the findings of previous research, 94,95 participants enjoyed the after-school sessions. Exposing girls to activities that they find enjoyable is crucial, as girls are more likely to participate in PA over the longer term if they find the activity enjoyable.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Similarly to the findings of previous research, 94,95 participants enjoyed the after-school sessions. Exposing girls to activities that they find enjoyable is crucial, as girls are more likely to participate in PA over the longer term if they find the activity enjoyable.…”
Section: Discussionsupporting
confidence: 66%
“…Girls have previously reported that they would be more likely to attend a session if their friends encouraged them to go. 19 In the current study, girls described enjoying 39,94,95 Aspects that were enjoyed by girls included learning new dance material, group work and dancing to current music. The perceived levels of exertion for dance sessions were low, similar to findings from the BGDP feasibility trial in which average exertion was 3.5 (out of 10).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We have reported the design , randomized controlled feasibility trial outcomes (Jago et al, 2014), and aspects of process evaluation (Jago et al, 2015) of an extracurricular intervention (Action 3:30) aimed at increasing the physical activity of children in Years 5 and 6 of UK primary school (i.e., 9-11 years of age). Action 3:30 was conducted in 20 schools (10 intervention, 10 control) 5-day training program to develop the skills and resources needed to deliver an after-school physical activity club.…”
Section: The Action 3:30 Feasibility Trialmentioning
confidence: 99%
“…We have previously published part of the Action 3:30 process evaluation (Jago et al, 2015) that was restricted to analysis of data on trial recruitment, intervention attendance, participant perceptions of enjoyment, reasons for nonattendance, fidelity to session objectives, and school context, including competing after-school activities. Recent UK guidance on process evaluation of complex interventions supports the publication of multiple process evaluation papers to ensure sufficient coverage of the range of data and evidence collected (Moore et al, 2014).…”
Section: The Present Studymentioning
confidence: 99%